CCDC69 maintains genome integrity by regulating KIF2C/MCAK depolymerase activity and the stability of the chromosomal passenger complex - Didier Fesquet; Gabriel Rabeharivelo; Juliette van Dijk; Claude Prigent; Nathalie Morin; Sylvie Rouquier (Scientific Reports)
Abstract Accurate genome inheritance during cell division relies on a complex chromosome segregation mechanism. This process occurs once all the kinetochores of sister chromatids are attached to microtubules emanating from the opposite poles of the mitotic spindle. To control the precision of this mechanism, the Chromosome Passenger Complex (CPC) actively identifies and corrects improper microtubule attachments. The depolymerase activity of the kinesin KIF2C/MCAK at the kinetochores is involved in this process. CCDC69 is a poorly characterized protein, primarily identified as a regulator of central spindle assembly, whose overexpression prompts rapid microtubule depolymerization. Here, we show that CCDC69 is a cell-cycle regulated protein belonging to the Microtubule-associated Tumor Suppressor (MTUS) superfamily, and even slight deregulation of its expression induces severe early mitotic phenotypes. Myristoylation anchors CCDC69 at the plasma membrane, thus protecting microtubule network integrity. We found that CCDC69 microtubule depolymerization activity relies on KIF2C, with a fraction of CCDC69 localizing to the centromere. Importantly, we demonstrated that CCDC69 regulates the stability of the CPC by safeguarding its members from degradation during mitosis. In summary, our findings underscore CCDC69’s essential role as a mitotic regulator, which is crucial for maintaining the fidelity of chromosome segregation.